Trends in prevalence of leisure time physical activity and inactivity: results from Australian National Health Surveys 1989 to 2011 - Josephine Chau; Tien Chey; Sarah Burks‐Young; Lina Engelen; Adrian Bauman (Elsevier, 2017)
Abstract Objective: To examine trends in leisure time physical activity and inactivity in Australians aged 15 years or older from 1989 to 2011. Method: We used data from six Australian National Health Surveys conducted from 1989/90 to 2011/12 in which physical activity was assessed using comparable questions. Analyses examined trends in the prevalence of sufficient physical activity (≥150 minutes/week moderate‐to‐vigorous physical activity) and of inactivity (<30 minutes/week moderate‐to‐vigorous physical activity). Results: The proportion of sufficiently active adults was 39.2% in 1989 and 40.7% in 2011 with an overall declining trend of 0.2% per year (p=0.012). The prevalence of inactivity was 38.7% in 1989 and 37.3% in 2011; the overall time trend by year was stable (OR=0.999, p=0.242). In women, sufficient physical activity decreased by 0.3% per year from 35.5% in 1989 (p=0.025); inactivity increased from 39.5% by 0.3% per year (p=0.004). In men, sufficient physical activity prevalence was 43.1% in 1989 with a steady trend; inactivity decreased from 37.9% by 0.5% per year (p<0.0001). Conclusions: The prevalence of sufficient physical activity remains low and inactivity high. Women appear to be a key target group for intervention. Public health efforts have been ineffective over two decades for improving physical activity among Australian adults. Implications for public health: This research supports calls for a national physical activity action plan given the multitude of benefits from sufficient physical activity. Maintenance of consistent physical activity questions in future National Health Surveys will facilitate long term tracking of physical activity levels in the Australian population.